Users’ feedback about the use of a telemedicine system during emergencies - Kyriacou, Efthyvoulos C.; Iolie Nicolaidou; Christou, Synesios; Nikolaou, Chrysovalantis; Mavrocheilos, Rafail; Spyrou, Giorgos; Neophytou, Michael S.; Constantinou, Riana (My University, 2016)
Support of Emergency cases handling using telemedicine systems is an issue of publication and research efforts for years. The goal of this study is to present feedback from the actual use of an emergency telemedicine system from paramedics and doctors working with emergencies. The feedback of 72 paramedics and doctors was solicited after the use of the system during a professional exercise and their input will be used for further improvement of the telemedicine system.
Keywords: Emergency; Telemedicine; Training; Users’ feedback